2016
DOI: 10.1007/s00253-016-7342-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of catalytic properties of multiple β-glucosidases of Trichoderma reesei

Abstract: Ten putative Trichoderma reesei β-glucosidase (BGL) isozymes were heterologously expressed in Escherichia coli and Aspergillus oryzae and purified to homogeneity. Catalytic properties of nine enzymes which showed hydrolytic activity on cellobiose and p-nitrophenyl-β-D-glucopyranoside (pNPG) were investigated. Three BGLs, encoded by the genes cel3A, cel3B, and cel3E, contained a predicted signal peptide, showed higher hydrolytic activity on cello-oligosaccharides than on pNPG, and preferred longer oligosacchari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 25 publications
4
40
1
Order By: Relevance
“…cel3D, a putative intracellular β-glucosidase, was expressed at a lower level in a T. reesei mutant with the deletion of β-glucosidase regulator bglR than the parental strain PC-3-7, when cellobiose was used as the carbon source [20]. The purified cel3D that was heterologously expressed in E.coli displayed very low enzyme activity towards cellobiose and other oligosaccharides [15]. Clearly, very few studies have been performed on cel3D and the role of cel3D on the cellulase production remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cel3D, a putative intracellular β-glucosidase, was expressed at a lower level in a T. reesei mutant with the deletion of β-glucosidase regulator bglR than the parental strain PC-3-7, when cellobiose was used as the carbon source [20]. The purified cel3D that was heterologously expressed in E.coli displayed very low enzyme activity towards cellobiose and other oligosaccharides [15]. Clearly, very few studies have been performed on cel3D and the role of cel3D on the cellulase production remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, cel3A (bgl1) is the major extracellular β-glucosidase in cellulase production [5], while cel1A (bgl2) [13] and cel1B [14] are intracellular. In addition, it is presumed that cel3B, cel3E, cel3F, cel3G and cel3H are extracellular, while cel3C, cel3D and cel3H are intracellular [15]. The involvement of β-glucosidases in cellulase production has been studied by characterization of mutants with knockout of different β-glucosidases.…”
Section: Introductionmentioning
confidence: 99%
“…18 For example, xylanases, for which this method has been successfully used, have a molecular weight of 20 kDa, 19,20 while the βgls secreted by Trichoderma reesei have estimated molecular weights ranging from 55 to 130 kDa. 21 Derivation of the apparent pK a values of the catalytic residues from the pHactivity profile 22 is also not trivial because interaction with other ionizable residues in the active site causes deviation from ideal titration behavior. 23 An alternative approach to these experimental methods is constant pH molecular dynamics (CpHMD), which captures fluctuations in the protonation state of ionizable residues caused by changes in solution pH and local conformation.…”
mentioning
confidence: 99%
“…28,29 This study investigated the role of active site residue pK a s on the H/T partition of the Hypocrea jecorina (teleomorph of T. reesei) GH3 βgl, Cel3A (HjCel3A), using CpHMD/pH-REX. HjCel3A, along with HjCel3B, exhibits the highest activity against cellobiose among the H. jecorina GH3 βgls 21 and was found to improve the conversion of various cellulosic substrates by nearly 10%. 30 However, its hydrolytic activity decreases at high cellobiose or glucose concentration because of increased transglycosidic activity, 21 which appears to be prevalent among GH3 βgls.…”
mentioning
confidence: 99%
“…5,6,[9][10]15 Several studies indicated that the downstream hydrolysis products (i.e., cellobiose, glucose and oligosaccharides) could be further consumed, and other disaccharides and/or oligosaccharides may synthesized by transglycosylation reaction of multifunctional cellulase. More specifically, during cellulose degradation process, the hydrolysis products of cellobiose and/or glucose are quickly consumed as substrates by transglycosylation to produce gentiobiose, spohorose, laminaribiose, and other disaccharides and oligosaccharides.…”
Section: The Significance Of Transglycosylation Harboring Cellulasementioning
confidence: 99%